ONLINE TRANSPORTATION SERVICES: FACTORS AFFECTING CONSUMER SWITCHING BEHAVIOR - Pieters, Virginia P.; Saerang, David P.E.; Gunawan, Emilia M. (Universitas Sam Ratulangi, 2019)
Abstract: The development of transportation in the revolution era 4.0 is increasingly rapid and one of the example is on demand services. Online transportation services have become public consumption. Gojek and Grab compete to get more customers, as well as maintaining their regular customers to not switch to competitor. Consumer switching behavior can occur if the company does not pay attention to several factors. This study aims to analyze the factors that affecting consumer to do the switching behavior. This research is using quantitative research method and use binary logistic regression analysis. This research is using purposive sampling with 100 respondents as a sample. The result shows that service encounter failure significantly affecting the consumer switching behavior. So, it is better for service provider to pay more attention to the human capital such as make a training program for each drivers.Â Keyword: transportation, online transportation services, consumer behavior, consumer switching behavior